Information acquisition differences between experienced and novice time trial cyclists - Boya, M.; Foulsham, T.; Hettinga, F.; Parry, D.; Williams, E.; Jones, H.; Sparks, A.; Marchant, D.; Ellison, P.; Bridge, C.; McNaughton, L.; Micklewright, D. (Medicine & Science in Sports & Exercise, 2017)
PURPOSE: To use eye-tracking technology to directly compare information acquisition behavior of experienced and novice cyclists during a self-paced, 10-mile (16.1 km) time trial (TT).